Transitioning ESTS - Aalok Khandekar; Grant Otsuki; Clément Dréano; Noela Invernizzi; Ali Kenner; Angela Okune; Duygu Kaşdoğan; Sujatha Raman; Tim Schütz; Federico Vasen; Amanda Windle; Emily York (Engaging Science, Technology, and Society)
Contributions to this issue focus on a wide range of domains and problematics—environment, extractivism, air pollution, climate change, digitalization, automation, care, surveillance—that offer a thought-provoking commentary on the many issues that inhabit contemporary intersections of science, technology, and society. It seems more than ever, we need sharp analyses that can help us understand, too, the ways global and national power struggles leverage and impact specific knowledge communities. We also reflect on the journal’s work throughout 2024, in this final issue for Volume 10. We also give our thanks to our funders and reviewers that have helped sustain a creative volume for 2024!